1990
DOI: 10.1021/ef00024a005
|View full text |Cite
|
Sign up to set email alerts
|

Role of nickel and vanadium in petroleum classification

Abstract: A common problem in petroleum exploration is how to predict the source of a petroleum accumulation or a surface seepage when there are no source rock data available. There is a need to be able to determine source type from petroleum properties alone, and to this end, an oil classification scheme has been devised. This is based initially upon relatively simple petroleum properties such as API gravity, sulfur content, etc., and enables classification to be made where relatively few other data are available as is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
156
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 282 publications
(169 citation statements)
references
References 0 publications
6
156
0
7
Order By: Relevance
“…Udo et al, 1992, reported that the V/Ni ratio decreases with increasing maturity. The lower V/Ni ratios are typically of terrestrially derived source rocks (Barwise, 1990;Udo et al, 1992 andNwachukwu et al, 1995). This suggests that the former groups of samples are more matured than the later.…”
Section: Ratios Of Transition Metalsmentioning
confidence: 99%
See 4 more Smart Citations
“…Udo et al, 1992, reported that the V/Ni ratio decreases with increasing maturity. The lower V/Ni ratios are typically of terrestrially derived source rocks (Barwise, 1990;Udo et al, 1992 andNwachukwu et al, 1995). This suggests that the former groups of samples are more matured than the later.…”
Section: Ratios Of Transition Metalsmentioning
confidence: 99%
“…These ratios are used in the determination of source rocks types, depositional environment and maturation of crude oils. This is because these ratios remain unchanged irrespective of digenetic and inreservoir alteration (Lewan, 1984;Barwise, 1990 andUdo et al, 1992).…”
Section: Ratios Of Transition Metalsmentioning
confidence: 99%
See 3 more Smart Citations